A Longitudinal Study of Parenting Style and Child Weight with Moderation by American Indian Ethnicity. (2nd October 2019) - Rutledge, Julie M.; Harrist, Amanda W.; Hubbs-Tait, Laura; Larzelere, Robert E.; Topham, Glade L.; Shriver, Lenka H.; Swindle, Taren
SYNOPSIS: Objective : Early childhood weight predicts later weight, so there is need for longitudinal research to identify key factors in the development of childhood obesity, especially among vulnerable populations. Design : This study examines the links between parenting styles and child obesity across three waves ( M ages = 6.90, 7.34, and 8.28 years) and the moderating factor of mother ethnicity in a sample of 356 children and their mothers (78.5% European American; 14.8% American Indian). Results : Growth curve SEM showed that high-permissive parenting predicted higher initial weight than the average permissive reference group and low permissive parenting group. Children of high authoritarian mothers began at a non-significantly different weight relative to the average authoritarian and low authoritarian reference groups, but later increased their weight, primarily from wave 1 to 2. An interaction between mother ethnicity and authoritative parenting was found for the autonomy granting subscale. Children of American Indian mothers with low levels of autonomy granting had the highest initial levels of weight compared to children of parents in the average and high autonomy granting reference groups and by wave 3 had an average increase close to the cutoff for being overweight. Conclusions : Parenting style appears to play a role in predicting child weight longitudinally, and this relation is moderated by the ethnicity of the child's mother. This study is also the first to show measurement invariance in the Parenting Styles and Dimensions Questionnaire among American Indian mothers.